1999
DOI: 10.1038/sj.bjc.6690420
|View full text |Cite
|
Sign up to set email alerts
|

A prospective multicentre study in Sweden and Norway of mental distress and psychiatric morbidity in head and neck cancer patients

Abstract: Summary A Swedish/Norwegian head and neck cancer study was designed to assess prospectively the levels of mental distress and psychiatric morbidity in a heterogeneous sample of newly diagnosed head and neck cancer patients. A total of 357 patients were included. The mean age was 63 years, and 72% were males. The patients were asked to answer the HAD scale (the Hospital Anxiety and Depression scale) six times during 1 year. The number of possible or probable cases of anxiety or depression disorder was calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
198
6
9

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(231 citation statements)
references
References 40 publications
18
198
6
9
Order By: Relevance
“…Hammerlid et al studied 357 head and neck cancer patients prospectively and found that women had significantly higher levels of anxiety at diagnosis as well as at one year follow-up than men. Similar finding was reported in regard to age, where younger patients were significantly more anxious than older patients (67). In another prospective study to assess fear of recurrence among orofacial cancer patients; females had also high levels of anxiety compared to males at 3 months following treatment (89).…”
Section: Psychological Distresssupporting
confidence: 66%
See 1 more Smart Citation
“…Hammerlid et al studied 357 head and neck cancer patients prospectively and found that women had significantly higher levels of anxiety at diagnosis as well as at one year follow-up than men. Similar finding was reported in regard to age, where younger patients were significantly more anxious than older patients (67). In another prospective study to assess fear of recurrence among orofacial cancer patients; females had also high levels of anxiety compared to males at 3 months following treatment (89).…”
Section: Psychological Distresssupporting
confidence: 66%
“…This cut-off is validated and commonly used in the literature to detect all possible cases of anxiety and depression (66)(67)(68) The HAD scale was designed and widely used as a screening instrument because it is a brief self assessment tool. In 2002, Bjelland et al reviewed 747 papers that used the HAD scale and confirmed its ability as a screening tool for detecting anxiety and depression (69).…”
Section: Sample Sizementioning
confidence: 99%
“…The use of alternative medicine and the treatment delay caused by that has been well-documented in the past [9,22,23]. In the developed countries, the use of alternative medicine is primarily attributable to the psychological distress over potential, often mutilating treatments [24,25]. However, in our study the consultation of unqualified local practitioners/alternative medicine could be attributed to the sheer ignorance and lack of primary health care facilities as most of such consultations were sought by the individuals with low literacy levels/who had no access to a PHC/who were unaware of their probable diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study 8 found that across six points of measurement during one year, the rate of anxiety among esophagus or gastroesophageal junction cancer patients was 16% to 34% while for depression the scores were a little bit higher and ranged from 27% to 44%. The main conclusion of the study was that psychiatric morbidity is common among esophageal cancer patients, both at inclusion and over time 8,9 . Summarizing reviews of depression in cancer raise a challenge as depressive symptoms occur on a broad spectrum that ranges from sadness to major affective disorder and because affect changes drastically making it difficult to assess when a patient is in a constant threat for life 10 .…”
Section: Introductionmentioning
confidence: 99%